Implementing semantic search for textual data in web applications - Toh, Jeremy Gen Yang (Nanyang Technological University, 2024)
Semantic search, also known as vector search, retrieves data based on their semantic similarity. It is enabled by sentence embeddings, which are high-dimension vectors that encapsulate the semantic meaning of sentences. Compared to traditional keyword search, semantic search accounts for the true intent of user queries which keyword search struggles to capture.